Infrastructure Development: Experience and Policy Options for the Future - Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 2002)
Global markets for goods and services have opened for countries that have made substantial investments in technological innovations in transportation, communications and production techniques, inventory management and the rapid rate of innovation in financial instruments, among others. This study presents in broad strokes a chronicle of infrastructure development in the Philippines in the last twenty-five years. It covers the infrastructure experience across the Marcos regime to the Estrada administration. The main objective of this paper is to flag those gaps and issues for future research, policy analysis and policy formulation. It calls particular attention to several constraints, e.g., large budget deficits faced by the national government, inefficient government implementation of infrastructure projects, unclear policy and regulatory framework for private participation in infrastructure. Among others, it brings attention to the design of the regulatory framework for infrastructure that would be necessary to motivate private sector participation. It is important to consider an appropriate regulatory framework to ensure fair competition, adequate returns to the private investor and consumer welfare. It is equally important to develop the appropriate incentives that should inform that regulatory framework.
Keywords: 330; private sector participation; infrastructure development; infrastructure policy; regulatory framework; incentive structure; Infrastruktur; Infrastrukturpolitik; Infrastrukturinvestition; Öffentlich-private Partnerschaft; Philippinen